Moldova Trade Study : Note 3. Competitiveness in Moldova’s Agricultural Sector - World Bank (Washington, DC, 2016)
The agriculture and agri-food sector is a substantial driver of Moldova’s international trade and export competitiveness. Enhancing Moldova’s agricultural competitiveness is a key element in improving the access of Moldovan agro-food products to the European Union market and capitalizing on the potential benefits from the Association Agreement, including the Deep and Comprehensive Free Trade Agreement (DCFTA). The objective of this note is to examine the competitiveness of Moldova’s agriculture sector, and synthesize relevant research on drivers and recommendations on improving agricultural competitiveness in Moldova, for policy makers. This note examines numerous studies that have been done to date on Moldova’s agriculture sector and its export competitiveness, synthesizes the findings, and presents recommendations. In order for significant exports to the EU to become reality, Moldova’s famers and exporters will need to adhere to the high product quality standards and traceability required in these markets, improve the quality of packaging, and in some cases, adjust the grading specifications. Achieving this requires actions to improve practices during growing and harvest; improve post-harvest handling and infrastructure; and improve the flow of market information and requirements to producers.